DESIGN OF LOW-LOSS TEM COAXIAL CAVITY BANDPASS FILTER - Zakaria, Z; Sabah, A (2012)
This paper presents a design of coaxial cavity bandpass filter that utilizing the method of tapped-input coupling. The design procedures have assumed lossless lowpass prototypes, thus yielding lossless bandpass filters. A systematic filter development using lowpass prototype as a starting point to produce four-pole Chebyshev bandpass response is demonstrated. The coaxial cavity filter has the center frequency of 2.5 GHz and bandwidth of 160 MHz. The insertion loss of 0.1 dB insertion loss and return loss better than 20 dB is achieved especially in the passband. This class of filter would be useful in microwave systems where the low insertion loss and high selectivity are crucial, such as in a base station, radar and satellite transceivers.